2012
DOI: 10.5586/aa.2005.024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of some growing media on the growth of strawberry cvs. 'Camarosa' and 'Fern'

Abstract: S u m m a r yThis study evaluated the development of above and under ground parts of strawberry plants cvs. Fern and Camarosa in a glasshouse using perlite, forest soil, finpeat, peat, finpeat+perlite (1:1) and peat+perlite (1:1) as substrates. The effects of different growing media on development of above and under ground parts of plant were statistically significant. The highest number of primary roots per plant, length of the most developed roots and number of crowns per runner were obtained from perlite, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 3 publications
2
16
0
Order By: Relevance
“…The substrate containing 50% of coconut chips and 50% of peat brick showed better properties for strawberry cultivation, which translated into the quantity and quality of the fruit yield obtained. Results achieved confirm findings of other authors, who demonstrated substantial differences in the assessed parameters of plants as affected by substrate type (Ercisli et al, 2005;Wang, Millner, 2009;Jafarnia et al, 2010;Roosta, Afsharipoor, 2012;Martinez et al, 2013). Research conducted by many authors (Ameri et al, 2012;Ebrahimi et al, 2012) point to higher yields of strawberries cultivated in the substrate containing coconut.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The substrate containing 50% of coconut chips and 50% of peat brick showed better properties for strawberry cultivation, which translated into the quantity and quality of the fruit yield obtained. Results achieved confirm findings of other authors, who demonstrated substantial differences in the assessed parameters of plants as affected by substrate type (Ercisli et al, 2005;Wang, Millner, 2009;Jafarnia et al, 2010;Roosta, Afsharipoor, 2012;Martinez et al, 2013). Research conducted by many authors (Ameri et al, 2012;Ebrahimi et al, 2012) point to higher yields of strawberries cultivated in the substrate containing coconut.…”
Section: Discussionsupporting
confidence: 90%
“…Using coconut as a substrate produced good results in plant cultivation owing to its high water capacity and appropriate air conditions (Stamps, Evans 1997). The research conducted so far has pointed to the direct influence of the applied substrate on the growth and development of plants (Ercisli et al, 2005;Ayesha et al, 2011) as well as on yield quality (Yavari et al, 2008). This necessitates the search for the appropriate type of medium for the cultivation of a particular plant species.…”
Section: Introductionmentioning
confidence: 99%
“…The number of leaves decreased as the soil amount increased in the media (Selda and Anapali, 2010). Similarly Ericisli et al, (2005) also reported soilless substrates were effective on growth of strawberry cultivars in terms of above and underground parts of plants. But the contrasting results were reported by Selda and Anapali, 2010, according to them perlite contain 6.9% aluminum which at low pH may be released into the solution and adversely affect the growth of strawberry plants.…”
Section: Resultsmentioning
confidence: 72%
“…In our experiment, the medium with perlite had a negative effect on the number of shoots in October. Similarly, E r c i s l i et al [19] obtained strawberry 'Fern' with a higher number of runners and with a higher number of crowns on runners in peat than in medium with peat and perlite (1:1 v:v).…”
Section: Discussionmentioning
confidence: 83%